Publication Trends on Higher-Order Thinking Skills and Science Process Skills in Elementary Schools (1992–2023): A Bibliometric Analysis of Science Education - Nugroho, Irham; Wilujeng, Insih; Pujaningsih; Sad Iman, Muis; Nadya Mahesawati, Putri (UIN Sunan Kalijaga Yogyakarta, 2025)
This study examines publication trends and thematic developments in research on Higher-Order Thinking Skills (HOTS) and Science Process Skills (SPS) in elementary science education. A bibliometric approach was employed to analyze Scopus-indexed publications from 1992 to 2023, using title, abstract, and keyword searches with queries such as (